Job Fair Program Implementation As An Employment Treatment In Sidoarjo District: Implementasi Program Job Fair Sebagai Upaya Penanggulangan Pengangguran Kabupaten Sidoarjo - Kamila Mashitho (Academia Open, 2020)
This research aims to analyze the implementation of job fair program as an effort to combat unemployment in Sidoarjo Regency. The type of research used is descriptive qualitative. Data collection techniques are carried out through observation, interviews and documentation. Determination of informants using purposive sampling techniques. Data analysis techniques are carried out by data collection, data reduction, data presentation, and conclusion drawing. The results showed that the Implementation of The Job Fair Program in the Sidoarjo Regency Labor Office has not been optimal because the communication of the Manpower Office is not maximal, human resources are sufficient because in its implementation does not require too many people involved, the authority of the Manpower Office only as the organizer of the job fair for the decision remains on the company. Keywords: Job Fair, Government-Private Cooperation, Unemployment Prevention.